The Mining Boom and Indigenous Labour Market Outcomes - Dockery, Alfred Michael (Springer, 2014)
Globalisation and rapid social and environmental change in recent decades have brought into sharper focus not only the benefits but also the costs of economic development. The once assumed link between economic development and societal well-being is being increasingly questioned in the face of growing social and environmental problems and unfulfilled expectations concerning political and commercial decision-makers. The orthodox development dogma is being tested in particular in resource-based economies such as Western Australia, where globalisation pressures and the concomitant rise in the demand for natural resources highlight the difficulties of effectively balancing broader societal interests with those of industry and the state. This book provides a critical review of the socio-political, environmental and cultural state of play in Western Australia, offering an analysis of how resource-based developments are shaping the state and its people